2010 International Conference on High Performance Computing 2010
DOI: 10.1109/hipc.2010.5713198
|View full text |Cite
|
Sign up to set email alerts
|

Trends and effects of energy proportionality on server provisioning in data centers

Abstract: Abstract-Cloud is the state-of-the-art back-end infrastructure for most large-scale web services. This paper studies what effect energy proportionality has on the energy savings of cloud data center management, under various equipment compositions and power densities. Our findings show that although it is a common expectation that improved energy proportionality should diminish the benefits of power management's server provisioning, this is not true in all cases. Results show that equipping server provisioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…These locations correspond to the location of three major Google data centers. We used the historical electricity prices for the above locations [117] (see Fig. 5.3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These locations correspond to the location of three major Google data centers. We used the historical electricity prices for the above locations [117] (see Fig. 5.3).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to design thermal aware server and workload management schemes to avoid the cooling-computing power tradeoff [16,44,117]. In general, the active server set selection affects the total power of the data center due to the non-uniform temperature distribution in the room (because servers do not equally impact the temperature in the room, nor are the airflow patterns symmetric) and the servers' heterogeneity in terms of their power and computing performance.…”
Section: (B) According To the Recent Uptimementioning
confidence: 99%
See 1 more Smart Citation
“…This is an issue because typical servers are not very energy efficient under low utilization. In [4], Varsamopoulos et al define two metrics to quantify energy proportionality: IPR, for Ideal to Peak Ratio, which measures the dynamic power range, and LDR, for Linear Deviation Ratio, to evaluate the linearity of the consumption. They studied the evolution of energy proportionality and found that recent servers feature better characteristics, but most time it only concerns one aspect: a larger dynamic power range or an improved linearity.…”
Section: Related Work On Energy Proportionalitymentioning
confidence: 99%
“…There are research studies that try to map the yeilded curve to a polynomial, most usually a linear function. Although a linear model is not always accurate [45] it has been extensively used due to its simplicity.…”
Section: Characterizing G C I Functionmentioning
confidence: 99%